ANALYSIS OF THE ADVANTAGES AND DISADVANTAGES OF 2D MODELSIN LEARNING MEDIA - nesti evriyanti (CV Grasta Glory, 2026)
Learning media plays an important role in helping students understand the material more easily. One of the media frequently used in learning activities is a two-dimensional (2D) model or mockup. A 2D model/mockup is a visual medium that displays objects in the form of flat images, helping students understand concepts more clearly. This article aims to explain the meaning of 2D models/mockups in learning media and analyze their advantages and disadvantages in the learning process. The method used in writing this article is a literature study by reviewing various book and journal sources related to learning media. The results of the study indicate that 2D models/mockups have several advantages, such as being easy to make, relatively inexpensive, and able to help students understand the material visually and increase learning interest. However, 2D models/mockups also have several disadvantages, namely they cannot display objects realistically like three-dimensional media, the information conveyed is limited, and they are less interactive compared to digital-based learning media. Therefore, the use of 2D models/mockups should be combined with other learning media to make the learning process more effective and interesting for students.